1986
DOI: 10.1073/pnas.83.19.7358
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of the human and mouse prion protein genes to homologous chromosomes.

Abstract: Purified preparations of scrapie prions contain one major macromolecule, designated prion protein (PrP). Genes encoding PrP are found in normal animals and humans but not within the infectious particles. The PrP gene was assigned to human chromosome 20 and the corresponding mouse chromosome 2 using somatic cell hybrids. In situ hybridization studies mapped the human PrP gene to band 20p12----pter. Our results should lead to studies of genetic loci syntenic with the PrP gene, which may play a role in the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0
5

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(70 citation statements)
references
References 36 publications
(36 reference statements)
2
61
0
5
Order By: Relevance
“…A study on the correlation between the murine prion protein sequence and length of scrapie incubation period suggested that the Prn-i gene was linked to or congruent with the murine prion protein gene (Prn-p) which encoded the prion protein. These genes from the prion gene complex were located on chromosome 2 (Sparkes et al, 1986). Studies of the nucleotide sequence of the Prn-p gene of inbred mouse strains revealed substitutions at codons 108 and 189 (Westaway et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…A study on the correlation between the murine prion protein sequence and length of scrapie incubation period suggested that the Prn-i gene was linked to or congruent with the murine prion protein gene (Prn-p) which encoded the prion protein. These genes from the prion gene complex were located on chromosome 2 (Sparkes et al, 1986). Studies of the nucleotide sequence of the Prn-p gene of inbred mouse strains revealed substitutions at codons 108 and 189 (Westaway et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the human and mouse PrP genes within conserved syntenic groups (Sparkes et al 1986) and the presence of a PrP gene in chicken (Gabriel et al 1992) argue that the PrP gene existed before the speciation of mammals. In mammals, DNA sequences of the ORFs encoding PrP generally exhibit ∼90% similarity.…”
mentioning
confidence: 99%
“…These GϩC nonamers represent a motif that may function as a canonical binding site for the transcription factor Sp1 (203). Mapping of PrP genes to the short arm of Hu chromosome 20 and to the homologous region of Mo chromosome 2 argues for the existence of PrP genes prior to the speciation of mammals (204,205).…”
mentioning
confidence: 99%